A new mechanistic insight of DNA base adenine formation from pentamer HCN in the gas phase of interstellar clouds. Issue 1 (11th December 2019) - Benallou, Abdelilah
ABSTRACT: The mechanism formation of adenine is determinate in the gas phase, by using density functional theory (DFT) method at the B3LYP hybrid together with 6-311g(d, p) basis set level. Thus, we have investigated the structures and mechanisms pathway as well as the barrier energies involved in this study. The results indicate that adenine formation in the space of primitive Earth is very difficult of energetic point of view of both cases tautomers. In addition, the high activation energies induce a very late reaction, so this conclusion increases suggest that the components necessary for the origin of life may have been formed in stars or by the help of the heat of Earth throughout its geologic formation or in solution phase. Subsequently, the prebiotic syntheses of adenine product by oligomerization process under interstellar conditions is an inefficiently in the gas phase.